2002
DOI: 10.6009/jjrt.kj00003111387
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of DSA Images Using Gadolinium Contrast Agent(Originals)

Abstract: Most contrast agents used in digital subtraction angiography (DSA) are non-ionic iodinated contrast agents, which can cause severe side effects in patients with contraindications for iodine or allergic reactions to iodine. Therefore, DSA examinations using carbon dioxide gas or examinations done by magnetic resonance imaging (MRI) and ultrasound (US) were carried out in these patients. However, none of these examinations provided images as clear as those of DSA with an iodinated contrast agent. We experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Also, contrast material should be injected for CTA and DSA that may be contraindicated for a number of patients where those undergoing MRA should be MRI compatible. 57,62,63 Removal of bony parts were used in several studies in the preprocessing step. It should be noted that without a sufficient model or human supervision, some calcified lesions may also be omitted, which leads to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, contrast material should be injected for CTA and DSA that may be contraindicated for a number of patients where those undergoing MRA should be MRI compatible. 57,62,63 Removal of bony parts were used in several studies in the preprocessing step. It should be noted that without a sufficient model or human supervision, some calcified lesions may also be omitted, which leads to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) established the upper limit of the dose of Gd contrast medium for intravenous administration as 0.6 mL/kg. 5) A study indicated that the upper limit of the dose of Gd contrast medium to be administered into cerebral blood vessels was 65 mL. 6) In addition, another study performed the intra-arterial administration of Gd contrast medium at 1.7 mL/kg for endovascular embolism treatment in children with AVM, and reported that there were no complications, including renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Problems associated with gadolinium are its low viscosity, the fact that the high speed of pulmonary arterial blood flow makes it difficult to view the blood flow with fluoroscopy, and that the technique is more difficult than when performed with iodine contrast. The effect of gadolinium contrast has also been reported to be approximately one fifth that of an iodine contrast [9] ; however, when an increased amount of gadolinium contrast medium is used, it can cause renal dysfunction. However, according to the guidelines for the use of gadolinium contrast for patients with renal failure, as recommended by the Japan Radiological Society and the Japan Society of Nephrology, there is insufficient evidence to support the claim that renal function of GFR ≥60 mL/min/1.73 m 2 increases the risk of nephrogenic systemic fibrosis (NSF).…”
Section: Discussionmentioning
confidence: 99%